Areias de Vale de Santarém. Estratigrafia e Palinologia - Pais, João (2010)
The palynologic study of several boreholes for lignite prospection at the "Vale de Santarém sands" is presented. Height spores and 18 pollen forms have been identified. The quantitative and qualitative results are shown in table 2. Four palynologic associations (A - D) corresponding to climatic changes have been characterized. Correlations are established with the plant associations of Rio Maior Basin. Correlation between the boreholes allow a better understanding of the small, Vale de Santarém basin infilling.